«HUMANITARIANS AT WAR»: ASSESSING THE ROLE OF THE INTERNATIONAL COMMITTEE OF THE RED CROSS IN THE IMMEDIATE AFTERMATH OF WWII - G. A. Bayazitova; G. A. Nelaeva; G. R. Sufiyanova (Vestnik MGIMO-Universiteta, 2018)
Book review: Steinacher, Gerald. Humanitarians at War. The Red Cross in the Shadow of the Holocaust, Oxford: OUP, 2017, 330 pp.  The book under review is written by Gerald Steinacher, a researcher from Nebraska-Lincoln University and deals with the analysis of the International Committee of the Red Cross (ICRC) activities in the period of 1944-1950. Using a variety of sources (archives, newspaper articles, reports and personal notes by ICRC representatives), the author attempts to demonstrate how the ICRC was trying to overcome a serious moral, organizational and financial crisis it found itself in: because of its failures to respond to the Holocaust and its activities to assist the former Nazis, it not only compromised its reputation and status, but also lost credibility in the eyes of the leading states of that time.